IS THE PRINCIPLE OF JUSTICE RESPECTED IN THE IMPLEMENTATION OF CONVENTIONAL BEEKEEPING SUPPORT? (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
From 2023, conventional beekeepers will receive support for pollination of land areas. The amount depends on the land area and the number of hives. Hives must be registered and veterinary requirements must be met. In addition, the beekeeper must certify that the relevant landowner will allow the beekeeper’s bees to pollinate the landowner’s cultivated areas for five consecutive years. It sounds quite absurd. In addition, the amount of support in material terms is so small that the beekeeper must seriously consider whether the relevant areas will be available for five years before asking to allow the bees to pollinate the neighbor's crops. If not, the aid received will have to be repaid. In general, support measures for conventional beekeeping are currently implemented in such a way and to such an extent that it can be said that there is no support at all.Therefore, in order to preserve beekeeping as an industry, it is immediately necessary to: 1) radically change the procedure for granting support, 2) increase the amount of support to at least cover the costs of the pollination service provided to the farmer.